Quelle femme pour la République ? Le théâtre révolutionnaire et les représentations de la féminité - Wysłobocki, Tomasz (Romanica Silesiana)
What Woman for the Republic? Revolutionary Theatre and Representations of Femininity The aim of this article is to show the way women were represented in the revolutionary theatre of the times of Great Terror (1793—1794). After three years of social and political changes brought by the Revolution women are no longer shown as possessions of their families or husbands. Although marriage remains the focus of their existence, they all fight to have a good life and a good marriage with a respectful partner, rather than with an all-mighty master who despises them. Many of female characters we meet are very independent and self-conscious — especially the younger generation who are well aware of the possibility of divorce. Men change too; fathers no longer decide for their daughters, while unfaithful husbands improve their behaviour, as they all know that the basis of general and personal happiness is a happy marriage. Key words: family, French Revolution, theatre, women.